Gambaran Penggunaan Media Social Pada Remaja - Gusti Maulani Rici (Departement of Mathematics Education, 2021)
Social media is a digital platform that facilitates users to socialize with each other, be it communicating or sharing content in the form of writing, photos and videos. All the content that is shared will be open to the public in real time. Almost all of the people are internet users, especially teenagers. Already 98% of teenagers use social media. The purpose of this study was to determine the description of social media users in adolescent girls. The approach taken in this research is descriptive and qualitative, the data collection is by interview and observation. The subjects of this research are young women who are in high school. The results of the research that has been done is that the use of social media affects the concentration of the teenager